ANALISIS JEMBATAN PIPA PDAM BENTANG 40 M - Stenly Yohanis Wisi Ate; M.Afif Shulhan; Dimas Langga C.Galuh (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2024)
The provision of clean water is one of the basic human needs. In this context, the PDAM pipe bridge is an essential infrastructure that allows clean water to flow from the source to the point of use. The PDAM pipe bridge with a span of 40 meters plays a vital role in delivering clean water to various areas, especially those that are geographically difficult to access. The purpose of this study is to analyze the calculation of load results on a PDAM pipe bridge structure. Based on the load analysis of the bridge structure referring to SNI 1725:2016, the results can be obtained for the Dead Load Structural (MS) as follows: Model 1 (67.38 tons), Model 2 (5.077 tons), Model 3 (11.94 tons), Model 4 (50.11 tons), Model 5 (11.30 tons). The Additional Dead Load (MA) is as follows: Model 1 (5.65 tons), Model 2 (1.49 tons), Model 3 (1.15 tons), Model 4 (5.14 tons), Model 5 (7.20 tons). The Repair Load is as follows: Model 1 (1.8 tons), Model 2 (1.8 tons), Model 3 (1.6 tons), Model 4 (1.4 tons), Model 5 (1.8 tons). The calculations use a WF 250.125.6.9 steel profile.